-2•f(x+1)+6 = -2 |x+1| +6, which is NOT g(x).
-2•f(x+1)+3 = -2 |x+1| +3, which IS g(x).
Side note: you’re writing g(x) in terms of f(x), because f(x) is in the answer.
If you want to write f(x) in terms of g(x), then g(x) would be in the answer.
Answer:
x-int=-8, y-int=2,-4
Step-by-step explanation:
for the x-int
you set x to 0 then solve the equation to get -8
for the y-int
you set y(or in this case f(x)) to 0 then solve. You solve this by spilting this into 2 linear equations; x-2=0 and x+4=0, then you solve them both to get the two y-intercepts, 2 and -4
I think it’s -2.8
hope this helps :)
Answer:
5x-8/12y
Step-by-step explanation:
x+1
3y
+
x−2
4y
−(
x+3
/6y
=
30xy2−48y2
72y3
=
30x−48/72y
=
5x−8
/12y